Determinant Citra Merek dan Dampaknya pada Keputusan Pembelian Sabun Mandi - Rahayu Lestari; Elwisam Elwisam; Molina Molina (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2020)
This study discusses issues related to purchasing decisions. Respondents in this study are consumers who buy and use then provide an assessment in the form of answers to questionnaires (questionnaires) that researchers provide that are in the Territory Tangerang and Depok. Analytical technique used to answer the hypothesis in this study using descriptive analysis method and analysis Smart Partial Least Square (PLS) with program SmartPLS 3.0 software. The number of samples used are 100 respondents residing in Tangerang and Depok areas. The results conclude brand awareness has a negative role to the brand image, competitive advantage has a positive role to the brand image, and attitudes toward advertising have a positive effect on brand image. Brand image positively affects purchasing decisions.